2016
DOI: 10.1073/pnas.1520401113
|View full text |Cite
|
Sign up to set email alerts
|

Importin-7 mediates memory consolidation through regulation of nuclear translocation of training-activated MAPK in Drosophila

Abstract: Translocation of signaling molecules, MAPK in particular, from the cytosol to nucleus represents a universal key element in initiating the gene program that determines memory consolidation. Translocation mechanisms and their behavioral impact, however, remain to be determined. Here, we report that a highly conserved nuclear transporter, Drosophila importin-7 (DIM-7), regulates import of training-activated MAPK for consolidation of long-term memory (LTM). We show that silencing DIM-7 functions results in impair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…To understand the neural mechanism by which spaced learning induces memory consolidation, we investigated the MB neurons in the flies subjected to olfactory aversive single training or spaced training (3). Previous research has indicated that olfactory training induces the pERK in the nucleus (15), which could map the neurons activated by the training session.…”
Section: Expression Of Perk In γM Neurons Is Decreased During Spacedmentioning
confidence: 99%
“…To understand the neural mechanism by which spaced learning induces memory consolidation, we investigated the MB neurons in the flies subjected to olfactory aversive single training or spaced training (3). Previous research has indicated that olfactory training induces the pERK in the nucleus (15), which could map the neurons activated by the training session.…”
Section: Expression Of Perk In γM Neurons Is Decreased During Spacedmentioning
confidence: 99%
“…According to our previous study (Li et al, 2016 ), we found that LTM training (spaced training, four repeated training sessions with 15-min interval) significantly induces more nuclear translocation of pMAPK at a representative time point of consolidation (8-h after spaced training), compared with naive flies and flies subjected to non-LTM training (massed training, four repeated and consecutive training sessions). This data indicates that LTM training specifically causes pMAPK nuclear translocation in KCs.…”
mentioning
confidence: 67%
“…However, relatively slower progress has been made on how behavioral training-induced synaptic signals translocate into nucleus, which is a critical step to bridge the former two questions together. In a recent study, we found that DIM-7, an importin in Drosophila , plays a critical role in mediating nuclear translocation of pMAPK to initiate LTM consolidation (Li et al, 2016 ). In that study, we found that Kenyon cells (KCs), neurons of mushroom body (MB), are critical places for nuclear translocation of pMAPK signal in determining LTM consolidation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Miyashita et al 22 demonstrated that this ERKs activation is required for the increased expression of c-fos and dCREB2 during spaced training. Moreover, Li et al 45 suggested that translocation of ERKs1/2 to the nucleus of mushroom body neurons is required for the consolidation of this LTM after retraining. ERKs1/2 activity is also a key step in LTM induced by retraining in rodents.…”
Section: Discussionmentioning
confidence: 99%